Enhancement of the bioavailability of a novel anticancer compound (acetyltanshinone IIA) by encapsulation within mPEG-PLGA nanoparticles: A study of formulation optimization, toxicity, and pharmacokinetics - Wang, Qi (2018)
The Poly (ethylene glycol) methyl ether-block-poly (lactide-co-glycolide) (mPEG-PLGA) nanoparticles carrying acetyltanshinone IIA (ATA), a novel anti-breast cancer agent, were prepared by ultrasonic emulsion method to enhance the bioavailability and reduce the toxicity. Systematic optimization of encapsulation process was achieved using an orthogonal design. Drug efficacy analysis showed that ATA nanoparticles were as effective as free ATA against estrogen receptor positive breast cancer cells, but much less toxic towards human endothelial cells. Furthermore, in zebrafish, ATA nanoparticles displayed much lower toxicity than free ATA. More importantly, the blood concentration of ATA nanoparticles indicated by 24 hour-area under the curve (AUC0-24h) was 10 times higher than free ATA. These results indicated the potential of ATA-loaded mPEG-PLGA nanoparticles for the delivery of ATA in a clinical formulation, and their potential for use in tumor therapy in the future.